Toxicity of dishwashing liquids against the American cockroach, Periplaneta americana L. (Dictyoptera: Blattidae) - Reza, AM Saleh; Din, Md MI; Parween, Selina (University Journal of Zoology, Rajshahi University, 2012)
Dishwashing liquids viz. Vim and Trix at concentrations of 0.5, 1.0, 1.5 and 2.0% were toxic against the adult American cockroach, Periplaneta americana L. after 24-h of exposure. Knockdown effect of the detergents was found to be 70-78% by contact with both the detergents. Whereas, by dipping 100% of the cockroaches were knocked down and ultimately died at 24-h exposure. The LC50 values were calculated for contact toxicity were 1.490% for Vim and 0.883% for Trix. The results revealed that Trix is more toxic than Vim against the adult P. americana. Keywords: Dishwashing liquid; toxicity; Periplaneta americana. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9466 UJZRU 2010; 29(1): 51-55